Autumn fertilization with nitrogen improves nutritional status, cold hardiness and the oxidative stress response of Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) nursery seedlings - Andivia, Enrique; Márquez-García, Belén; VÁZQUEZ-PIQUÉ, JAVIER; Córdoba, Francisco; FERNÁNDEZ, MANUEL (Trees, 2011)
Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) is one of the most important species in forest communities of the western Mediterranean Basin, but is very vulnerable to environmental stress during the ﬁrst years of its life. In particular, summer drought and winter frosts limit the distribution, survival, and growth of Holm oak. These two stress factors can lead to plasmolysis and/or oxidative stress. We hypothesized that autumn fertilization with nitrogen (N) can improve plant tolerance to these abiotic stress factors and improve plant quality and therefore reforestation success. A 12-week autumn application of 30 or 60 mg N (plus 70 mg N applied to both treatments during the previous 28 weeks in the nursery, i.e. 100 and 130 mg N in total, respectively) improved overall growth, root growth capacity, frost tolerance, and nutritional status of plants relative to plants given 0.0 and 1.5 mg autumnal N, and had no negative effect on seedling response to water stress. A very small increment in N doses during the autumn (1.5 vs. 0.0 mg N) improved some morphological parameters, such as stem diameter (D) and shoot dry weight, and physiological parameters, such as total antioxidant activity. The highest autumnal N dose (60 mg) increased leaf nutrient content without decreasing the concentration, but had a tendency to reduce frost tolerance relative to seedlings given a lower autumnal N dose (30 mg).
Keywords: Frost tolerance; Holm oak; Mineral nutrients; Oxidative stress; water stress